NuA4 acetyltransferase is required for efficient nucleotide excision repair in yeast - Hodges, Amelia J. (DNA Repair (Amst), 2018)
The nucleotide excision repair (NER) pathway is critical for removing damage induced by ultraviolet (UV) light and other helix-distorting lesions from cellular DNA. While efficient NER is critical to avoid cell death and mutagenesis, NER activity is inhibited in chromatin due to the association of lesion-containing DNA with histone proteins. Histone acetylation has emerged as an important mechanism for facilitating NER in chromatin, particularly acetylation catalyzed by the Spt-Ada-Gcn5 acetyltransferase (SAGA); however, it is not known if other histone acetyltransferases (HATs) promote NER activity in chromatin. Here, we report that the essential Nucleosome Acetyltransferase of histone H4 (NuA4) complex is required for efficient NER in Saccharomyces cerevisiae. Deletion of the non-essential Yng2 subunit of the NuA4 complex causes a general defect in repair of UV-induced cyclobutane pyrimidine dimers (CPDs) in yeast; in contrast, deletion of the Sas3 catalytic subunit of the NuA3 complex does not affect repair. Rapid depletion of the essential NuA4 catalytic subunit Esa1 using the anchor-away method also causes a defect in NER, particularly at the heterochromatic HML locus. We show that disrupting the Sds3 subunit of the Rpd3L histone deacetylase (HDAC) complex rescued the repair defect associated with loss of Esa1 activity, suggesting that NuA4-catalyzed acetylation is important for efficient NER in heterochromatin.